Динаміка адсорбційного розділення суміші іонів Сu2+ та Сr3+ в апараті колонного типу - Гумницький, Я. М.; Сабадаш, В. В.; Миляник, О. В.; Gumnitsky, J. M.; Sabadash, V. V.; Mylyanyk, O. V. (Lviv Politechnic Publishing House, 2018)
Експериментально досліджено адсорбційну ємність цеоліту щодо іонів Сu2+та Сr3+ в апараті колонного типу. Порівняно теоретичні розрахунки та результати експериментальних досліджень процесу сумісної адсорбції іонів Сu2+та Сr3+ цеолітом у динамічних умовах. Встановлено час захисної дії та час проскоку для різної висоти сорбенту. Наведено експериментальні дані динаміки адсорбції іонів Сu2+та Сr3+ цеолітом в апараті колонного типу. Розроблено принципову технологічну схему для розділення суміші катіонів важких металів для неперервного очищення стічних вод .

The adsorption capacity of zeolite for Cu2 + and Сr3 + ions in the fixed-bed column has been experimentally investigated. The comparison of theoretical calculations and the results of experimental studies of the process of simultaneous adsorption of copper and chromium ions on zeolite in dynamic conditions were presented. The exhaustion time and breakthrough time at different bed depth have been set. Experimental data of adsorption dynamics of Сu2+ and Сr3 on zeolite in the fixed-bed column were presented. The principal technological scheme for separating a mixture of heavy metal cations for continuous sewage treatment is developed.
Dynamic of adsorption seperation of Cu2+ and Cr3+ chromium (III) ions in the fixed-bed column
Keywords: хроматографія; динаміка адсорбції; технологічна схема; важкі метали; chromatography; adsorption dynamics; technological scheme; heavy metals